Agronomic performance of day-neutral strawberry cultivars as a function of early planting dates - Cappellesso, Adinor José; Cardoso, Francieli Lima; Scapin, Luana Carla; Miotto, Alcione (Revista de Ciências Agroveterinárias, 2025)
The cultivation of day-neutral strawberry plants combined with earlier planting dates in regions with mild winters can increase the supply of this fruit between May and September, when prices are at their highest in Brazil. In this context, the present study aimed to analyze the agronomic performance of four day-neutral strawberry cultivars as a function of the anticipation of the planting date in the municipality of São Miguel do Oeste, SC. The experiment was conducted in an umbrella-type greenhouse, on slabs with six plants and fertirrigated with a standard solution for the crop. The randomized block design was bifactorial (4x2), with: a) four cultivars: San Andreas®, Alpina10®, Bellalinda®, and BeautyTM (FL 12 1215®); and b) two planting dates: D1, on 03/10/2022; and D2, on 04/10/2022. The analysis leads to the conclusion that early planting resulted in greater total mass of commercial and defective fruit. While the total mass did not differ between cultivars, ‘San Andreas’ and ‘Alpina10’ had higher commercial mass. Bellalinda produced a greater number of fruits, which contributed to a smaller average size, increasing the number and mass of non-commercial fruits. Beauty showed higher commercial production from May to June. The expected economic results differed between cultivars, indicating the need to include the planting date variable in the analysis of genotypic potential. The cultivars ‘San Andreas’, ‘Beauty’, and ‘Bellalinda’ showed better economic results with early cultivation, while ‘Alpina10’ did not differ between the two dates.